Caractérisation géomécanique et évaluation en construction routière des matériaux pouzzolaniques de Kanyaruchinya (Nord-Kivu, R.D. Congo) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The objective of this work is to evaluate the geotechnical characteristics of pozzolanic materials from Kanyaruchinya in the Democratic Republic of Congo, in order to define the practical modalities of their use in road construction. After a detailed macroscopic description of the materials in the field, the taken samples were subject to a geotechnical identification. The geotechnical work focused on the realization of identification and compaction tests by reference to French standards. The obtained results show that the studied materials are porous and loose. The Kanyaruchinya pozzolanas are of vacuolar and scoriaceous structure, and present a variability of color going from brick red to dark brown, yellow and black due to the iron oxidation states. These materials consist of high gravel content (47–76%), moderate sand content (21–44%) and low to moderate pebble content (2–30%). With a maximum grain diameter (25–40 mm) smaller than 60 mm, these materials can be used in road construction without risk of segregation. The studied pozzolanas are less fine (3 % < C80µm < 4 %) and non-plastic. The CBR (California Bearing Ratio) of the studied pozzolana has an average value of 31%. These materials can be used as sub-base layer for low volume traffic T1 despite their maximum dry density (MDD) values lower than 1.80. This use is confirmed by their maximum grain diameter of less than 60 mm and grading modulus values between 1.65 and 2.70. The optimization of their use in sub-base layer for all volume traffics and in base course requires an improvement by adding a fine-grained, high-density material such as clay sand, sandy clay, clay lateritic. This operation could raise the MDD values. However, a compaction energy higher than that obtained for traditional materials is necessary for the implementation of these materials in their natural state.